1990
DOI: 10.1007/bf01289696
|View full text |Cite
|
Sign up to set email alerts
|

Quasifree processes in the3H+2H→d+d+n reaction

Abstract: The quasifree scattering and reaction processes in the 3H + 2H ~ d ~ d + n interaction leaving a neutron as a spectator have been investigated at incident triton energies around 35 MeV. The results compare well with the predictions from Plane Wave Impulse Approximation, arbitrarily normalized to the data. The final energy prescription was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It should be stressed that THM has its scientific background in the theory of the direct reaction mechanisms [19] the studies of the QF reaction mechanisms (see i.e. [20][21][22][23][24]), and it is an extension of the measurements of the excitation function of the three-body cross sections for QF reaction, at low energies [25][26].…”
Section: Basic Theory Of Trojan Horse Methodsmentioning
confidence: 99%
“…It should be stressed that THM has its scientific background in the theory of the direct reaction mechanisms [19] the studies of the QF reaction mechanisms (see i.e. [20][21][22][23][24]), and it is an extension of the measurements of the excitation function of the three-body cross sections for QF reaction, at low energies [25][26].…”
Section: Basic Theory Of Trojan Horse Methodsmentioning
confidence: 99%
“…The coincidence detection of two of the outgoing alpha particles showed that, in addition to the usual sequential decay through states of 8 Be, another mechanism contributed to the spectra, giving place to a bump centered at the minimum momentum of the undetected alpha. Angular correlations and energy sharing spectra showed that the shape of this bump was consistent with a contribution of the 5 He( 3 He, α) 4 He virtual reaction occurring in the frame of a quasi-free process.…”
mentioning
confidence: 99%
“…Of course no comparison with the free cross section could be done in the case of the 5 He( 3 He, α) 4 He reaction, due to the unbound nature of 5 He. Other light systems were experimentally studied in the following years (see for instance [5][6][7][8] and references therein), possessing in the entrance channel projectile or target with a marked ground state cluster structure, like 6 Li and 2 H and indication of a quasi-free mechanism was found in many cases. The case of the 6 Li( 6 Li, 2α) 4 He reaction [9] was particularly interesting since the α-d momentum distribution in 6 Li could be measured within the same experiment by selecting alternatively the events corresponding to the quasifree mechanism with the spectator either in the target or in the projectile.…”
mentioning
confidence: 99%